Minocycline treatment increases resistance to oxidative stress and extends lifespan in Drosophila via FOXO. - Lee, G.J.; Lim, J.J.; Hyun, S. (Oncotarget, 2017)
Minocycline is a semi-synthetic tetracycline derivative antibiotic that has received increasing attention for its non-antibiotic properties, mainly anti-inflammatory, tumor-suppressive, and neuroprotective effects. Drosophila is a widely used genetically tractable model organism for studying organismal aging by virtue of its short lifespan and ease of cultivation. In this study, we examined the effects of minocycline on Drosophila lifespan and its associated traits. Minocycline-supplemented food significantly extended lifespan in both Canton S and w1118 Drosophila strains. The drug-induced lifespan extension was not associated with reduced dietary intake or reduced female fecundity, but rather with increased resistance to an oxidative stressor (hydrogen peroxide). Notably, minocycline's effects on lifespan and resistance to oxidative stress were largely abrogated in Forkhead box O (FOXO) null mutant, and the drug treatment increased the activity of FOXO. These results may further our understanding of minocycline's beneficial effects against several age-associated deteriorations observed in animal models.